Understanding the Concept of Fractions through the Integration of the Realistic Mathematics Education Approach and Metacognition: A Descriptive Study of Second-Grade Elementary School Students in Indonesia - Rina Setiana; Karlimah Karlimah; Ika Fitri Apriani (Jurnal Pendidikan Terapan, 2026)
This study aims to analyze elementary school students’ understanding of fractional numbers through the application of a metacognitive-based Realistic Mathematics Education (RME) approach. The study employed a qualitative, descriptive approach and was conducted with second-grade students at SDN Banjarwangi. Research subjects were selected using purposive sampling. Data were collected through concept comprehension tests, observations, interviews, and documentation. Data analysis was performed using the Miles and Huberman interactive model, which includes data reduction, data presentation, and drawing conclusions, and its validity was tested through triangulation of techniques and sources. The research results indicate that students’ understanding of fraction concepts falls into the “good” category, with an average score of 79.4%, an increase from the pre-test score of 61.2%. Most students were able to restate the concepts, classify, and represent fractions, but still had difficulty explaining the solution procedures systematically. Results from interviews and observations indicate that the use of real-world contexts in the RME approach helped students understand the concepts more concretely, while metacognitive strategies encouraged students to plan, monitor, and evaluate their thinking processes. Thus, RME- and metacognition-based mathematics learning is effective in improving students’ understanding of fraction concepts, although reinforcement is needed in the area of mathematical communication. This study recommends the integration of real-world contexts and reflective activities in learning to enhance the quality of students’ conceptual understanding.